The Level of Efficiency of Islamic Rural Banks in Java 2014-2017 Using Slacks-Based Data Envelopment Analysis - Akhriza Halim; Teddy Oswari (Falah: Jurnal Ekonomi Syariah, 2020)
The purpose of the study is to evaluate the efficiency of Islamic rural banks in Java by looking at the factors that could influence it year 2014-2017. This research is quantitative using a non-parametric and non-radial based Data Envelopment Analysis method with an intermediation approach to evaluate efficiency. The object of this study is 72 Islamic rural banks in Java. The results indicates that the level of efficiency of Islamic rural banks in Java was still low.